Eksistensi Istihsan dalam Istinbath Hukum Menurut Perspektif Imam Hanafi - Winarno, Winarno (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
In this case talked about concideration about Islam law development in it’s accelaration and this case appear in modern time. The Research in this journal is the exprolation of the real thing that have done by Imam Hanafi. This research is a library research by taking and collecting data from the literature that correlleted with problem and how to discuss. The data of this research is kwalitative data that correlated with Imam Hanafi’s think about Istihsan.The result of this research showed that, Istihsan method excistence. In law Istinbath that used by Imam Hanafi is developing from Qiyas Khofi method, whereas this method is trying to look for one of Dalil (rules) from two Dalil (reules) that againts with other Dalil because it can get more achive the purpose of law form. So every case / problem that faced can have solution.